Dissolved Phosphorus Pools and Alkaline Phosphatase Activity in the Euphotic Zone of the Western North Pacific Ocean - Suzumura, Masahiro; Hashihama, Fuminori; Yamada, Namiha; Kinouchi, Shinko (Frontiers in Microbiology, 2012)
We measured pools of dissolved phosphorus (P), including dissolved inorganic P (DIP), dissolved organic P (DOP) and alkaline phosphatase (AP)-hydrolyzable labile DOP (L-DOP), and kinetic parameters of AP activity (APA) in the euphotic zone in the western North Pacific Ocean. Samples were collected from one coastal station in Sagami Bay, Japan, and three offshore stations between the North Pacific Subtropical Gyre (NPSG) and the Kuroshio region. Although DIP concentrations in the euphotic zone at all stations were equally low, around the nominal method detection limit of 20 nmol L−1, chlorophyll a (Chl a) concentrations were one order of magnitude greater at the coastal station. DOP was the dominant P pool, comprising 62–92% of total dissolved P at and above the Chl a maximum layer (CML). L-DOP represented 22–39% of the total DOP at the offshore stations, whereas it accounted for a much higher proportion (about 85%) in the coastal surface layers. Significant correlations between maximum potential AP hydrolysis rates and DIP concentrations or bacterial cell abundance in the offshore euphotic zone suggest that major APA in the oligotrophic surface ocean is from bacterial activity and regulated largely by DIP availability. Although the range of maximum potential APA was comparable among the environmental conditions, the in situ hydrolysis rate of L-DOP in the coastal station was 10 times those in the offshore stations. L-DOP turnover time at the CML ranged from 4.5 d at the coastal station to 84.4 d in the NPSG. The ratio of the APA half saturation constant to the ambient L-DOP concentration decreased markedly from the NPSG to the coastal station. There were substantial differences in the rate end efficiency of DOP remineralization and its contribution as the potential P source between the low-phosphate/high biomass coastal ecosystem and the low-phosphate/low biomass oligotrophic ocean.